Electrical properties of FeII‐terpyridine‐Modified cellulose nanocrystals and polycaprolactone/FeII‐CTP nanocomposites. Issue 9 (28th March 2015) - Hassan, Mohammad L.; Fadel, Shaimaa M.; Ward, Azza A.; Moorefield, Charles M.; Newkome, George R.
Abstract : Supramolecular crosslinked Fe II ‐terpyridine cellulose nanocrystals (Fe‐CTP) were prepared by surface modification of cellulose nanocrystals with 4′‐chloro‐2, 2′:6′, 2″‐terpyridine and subsequent reaction with Fe(II)SO4 . The prepared complex was characterized using transmission electron microscopy (TEM), ultraviolet spectroscopy (UV), thermogravimetric analysis (TGA), and measuring its electrical properties at temperatures from 25 to 70°C. Use of Fe‐CTP at loadings from 1% to 10% (wt. ratio) in nanocomposites with polycaprolactone polymer was investigated; the nanocomposites were characterized regarding their electrical properties, which studied using broadband AC‐relaxation spectroscopy in the frequency range between 0.1 Hz and 1 MHz. The results were compared to that of PCL nanocomposites containing multiwalled carbon nanotubes (CNT). Variation in real and imaginary parts of permittivity has been explained on the basis of interfacial polarization of fillers in the polymer medium. The percolation limit of the conductive CNT and Fe‐CTP as studied by ac conductivity measurements has also been reported. Fe‐CTP showed conductivity values in the range of semiconductors. PCL/Fe‐CTP nanocomposites showed conductivity values from 1.98 × 10 −11 to 3.76 × 10 −6 while PCL/CNT nanocomposites showed conductivity values from 1.4 × 10 −10 to 3.67 × 10 −4 S/m for 1–10 wt% CNT content. POLYM. COMPOS., 37:2734–2743, 2016. © 2015 Society of Plastics Engineers